Beyond the Determiner “Al-”: Expanding the Determiner Class in Arabic, and Elimination of Lexical Ambiguities by Grammars - Albatool Abalkheel; Alexis Amid Neme (IEEE Access)
Arabic nouns can be marked for definiteness or indefiniteness. The definite article is the prefix “Al-,” which confines the determiner class to a single element “Al-.” This topic is generally discussed under noun inflections, such as Gender, Number, Definiteness, and Case (GNDC), in grammar textbooks. The primary aim of this paper is to expand the Arabic determiner class (DET) by incorporating additional lexical items and providing a detailed description of their syntactic context within noun phrases (NPs). In traditional grammar, these lexical items are typically classified as noun adjectives and, at best, are referred to as noun specifiers since they modify the head noun. However, these “nouns” exhibit limited inflection compared to regular adjectives and occupy a specific position within the NP sequence. Additionally, the modified head nouns are constrained in their inflectional attributes, Number, and Definiteness. Our approach is qualitative and guided by morpho-syntactic considerations. We conduct an in-depth analysis of the grammatical features of ten lexical items, focusing particularly on the dependencies between the determiner and the following noun. This analysis also addresses some semantic properties. By focusing on context-sensitive grammatical rules, the study shows how these methods can enhance precision in parsing and reduce ambiguity in NLP tasks, highlighting the potential for developing more refined grammar for Arabic. This work is a prototype for comprehensive studies in linguistics and NLP.